Pemberdayaan Aparatur Desa dalam Peningkatan Kompetensi Hukum Pengadaan Barang dan Jasa di Desa Wonosalam Kabupaten Jombang: Pengabdian - Suheryadi, Bambang; Herini Siti Aisyah, Rr.; Yudha Hernoko, Agus; Kagramanto, Budi; Adhipramana, Fikri; Arnanda Mahantika, Nacha; Savero Rianda, Juan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The objective of this activity is to enhance the legal competence and technical capacity of village officials in managing the procurement of goods and services in a transparent, accountable manner, and in compliance with prevailing laws and regulations. Through interactive training, simulations, and regulation-based mentoring, village officials have gained comprehensive legal knowledge, as well as technical skills in needs assessment, cost estimation (HPS) preparation, contract drafting, and accountability reporting. This activity also fosters the confidence of village officials in making rule-based decisions and promotes a culture of transparency and accountability in village governance. The results are evident from the increasing openness of procurement processes to public monitoring and the improved readiness of villages to face external audits.Moving forward, capacity strengthening for village officials should be implemented sustainably through regular training, discussion forums, and inter-village knowledge sharing facilitated by local governments, universities, and supervisory institutions to realize clean, orderly, and participatory village governance.